2018
DOI: 10.1186/s12955-018-0869-z
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in children and adolescents with congenital diaphragmatic hernia: a cross-sectional study

Abstract: BackgroundPatients with congenital diaphragmatic hernia (CDH) have a high residual morbidity rate. We compared self-reported health-related quality of life (HRQoL) between patients with CDH and healthy children.MethodsForty-five patients with CDH who were born from January 1, 1990, through February 15, 2015, were matched to healthy, age-matched control participants at a 1:2 ratio. The health records of the study participants were reviewed to determine comorbid conditions, and HRQoL was assessed by both the par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
16
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 40 publications
4
16
1
Order By: Relevance
“…The two studies that reported a lower HRQoL in CDH survivors, Bojanić et al and Tan et al, were the only studies to use age-matched controls rather than normative data. 14,39 The study by Bojanić et al compared 45 CDH children with a mean age of 8.2 years with 90 age-matched controls without chronic diseases. 39 They used the PedsQL questionnaires for patients and parents.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The two studies that reported a lower HRQoL in CDH survivors, Bojanić et al and Tan et al, were the only studies to use age-matched controls rather than normative data. 14,39 The study by Bojanić et al compared 45 CDH children with a mean age of 8.2 years with 90 age-matched controls without chronic diseases. 39 They used the PedsQL questionnaires for patients and parents.…”
Section: Resultsmentioning
confidence: 99%
“…14,39 The study by Bojanić et al compared 45 CDH children with a mean age of 8.2 years with 90 age-matched controls without chronic diseases. 39 They used the PedsQL questionnaires for patients and parents. Patients and parents scored patients significantly lower than controls in physical and psychosocial domains.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations